The Expression Profile of Complement Components in Podocytes - Li, Xuejuan; Ding, Fangrui; Zhang, Xiaoyan; Li, Baihong; Ding, Jie (International journal of molecular sciences, 2016)
Podocytes are critical for maintaining the glomerular filtration barrier and are injured in many renal diseases, especially proteinuric kidney diseases. Recently, reports suggested that podocytes are among the renal cells that synthesize complement components that mediate glomerular diseases. Nevertheless, the profile and extent of complement component expression in podocytes remain unclear. This study examined the expression profile of complement in podocytes under physiological conditions and in abnormal podocytes induced by multiple stimuli. In total, 23/32 complement component components were detected in podocyte by conventional RT-PCR. Both primary cultured podocytes and immortalized podocytes expressed the complement factors C1q, C1r, C2, C3, C7, MASP, CFI, DAF, CD59, C4bp, CD46, Protein S, CR2, C1qR, C3aR, C5aR, and Crry (17/32), whereas C4, CFB, CFD, C5, C6, C8, C9, MBL1, and MBL2 (9/32) complement factors were not expressed. C3, Crry, and C1q-binding protein were detected by tandem mass spectrometry. Podocyte complement gene expression was affected by several factors (puromycin aminonucleoside (PAN), angiotensin II (Ang II), interleukin-6 (IL-6), and transforming growth factor-β (TGF-β)). Representative complement components were detected using fluorescence confocal microscopy. In conclusion, primary podocytes express various complement components at the mRNA and protein levels. The complement gene expressions were affected by several podocyte injury factors.